A review of animal models for studying bone health in type-2 diabetes mellitus (T2DM) and obesity - Norazman, Saiful Iqbal; Mohd Zaffarin, Anis Syauqina; Shuid, Ahmad Nazrun; Hassan, Haniza; Soleiman, Ima Nirwana; Kuan, Wong Sok; Alias, Ekram (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Preclinical research on diabetes and obesity has been carried out in various animal models over the years. These animal models are developed from genetic manipulation that affects their body metabolism, chemical-induced procedures, diet alteration/modifications, or combinations of the aforementioned approaches. The diabetic and obesity animal models have allowed researchers to not only study the pathological aspect of the diseases but also enable them to screen and explore potential therapeutic compounds. Besides several widely known complications such as macrovascular diseases, diabetic neuropathy, nephropathy and retinopathy, type 2 diabetes mellitus is also known to affect bone health. There is also evidence to suggest obesity affects bone health. Therefore, continuous research needs to be conducted to find a remedy or solution to this matter. Previous literature reported evidence of bone loss in animal models of diabetes and obesity. These findings, as highlighted in this review, further augment the suggestion of an inter-relationship between diabetes, obesity and bone loss.